Nature and Degree of Severity of Consultations in Gynecological Emergencies: A Tunisian prospective study - Aloui, Haithem; Azouz, Eya; Hatem, Frikha; Rami, Hammami; Hassine, Abouda Saber; Badis, Chanoufi (Indonesian Journal of Obstetrics and Gynecology, 2025)
AbstractIntroduction: Gynecological emergencies are often crowded with false emergencies. They overwhelm doctors who also have to manage the birth room. The main objective of our work was to assess the type and degree of severity of pathologies encountered in gynecological emergencies.Methods: This is a prospective descriptive study, carried out in the gynecological emergencies of the Mongi Slim hospital, Tunisia, from July 1 to July 21, 2023. We have defined the reality of the emergency as the main endpoint and we have classified the women in three groups: "real" emergencies, "legitimate" emergencies and "false" emergencies.Results:We included 179 patients. The average age of the consultants was 32 years old. They had no gynecological follow-up (83.8 percent) and consulted the emergency room on their own initiative (88.8 percent). They consulted most often for abdominopelvic pain (41.9 percent) and bleeding (28 percent). Pelvic ultrasound was almost always performed (87.7 percent), as well as plasma beta-HCG assay (45.3 percent). The patients were hospitalized in 14.5 percent of cases, readmitted to central emergency departments in 20.1 percent and sent home in 65.4 percent of cases. In the end, we found that only 11.1 percent of the emergency room consultants presented a real gynecological emergency.Conclusions:Better organization of primary care, improved university training in gynecology for future family physicians and better information for the population must be encouraged so as not to unnecessarily encumber the gynecological emergency departments.Key words : Emergencies, diagnosis, treatment, gynecology, ultrasound